Aflatoxins: Finding Solutions for Improved Food Safety by Andrew Emmott - Emmott, Andrew (2013)
IFPRI Policy Seminar "Aflatoxins: Finding Solutions for Improved Food Safety" held at IFPRI on November 5, 2013. Presentation by Andrew Emmott, Twin & Twin Trading.